Ordenamiento territorial de la cabecera cantonal del cantón Yacuambi perteneciente a la provincia de Zamora Chinchipe. - Paccha Tamay, Edy Alberto (2009)
The present investigative work focuses the use of the Geographical Information Systems (SIG) the Territory Classification in the head of the Yacuambi country belonging to the Zamora Chinchipe Province. With this outlook it has been carried out the evaluation of the susceptibility, the threat, the Vulnerability, and the risk in basis to a theoretical system, which consists in evaluating the biggest number in conditioning factors of the land quantitatively which them influence directly in the appearance of new geologic threats. It has been taken starting point topographical digital information of the study sector with scale to detail (1:1000); in basis to this information and with the field works carried out; it has been obtained thematic maps of: geology, geomorphology, slopes, current use of the land, use of the urban soil, precipitations, vegetation and inventory of slips. Each variable that constitutes each one of these thematic maps it has been valued in basis to the capacity that each one of them have to be prone to the movements in massive. With the help of the Geographical Information Systems, each variable has been fried in digital form and they was analyzed to involve the thematic maps and to obtain the final map where it shows the areas of use of the study area. This obtained information, in digital and similar form it will serve as basis to that the Municipality of Yacuambi Country can carry out the necessary orders, since in this information it describes the areas that where it can or it can`t carry out infrastructures or urbanizations it ending up to improve the life`s conditions of the population to its position therefore it pretends to arrive to the development of the 28 of May Parish and all at once it pretends top archive the manage of the resources so much human, as environmental and economic.